Oxford and Grenoble: multiple anchors, strong dyadic relationships and national policy in fostering cluster architectures. Issue 10 (3rd October 2022) - Assimakopoulos, Dimitris; Smith, Helen Lawton; Baines, Ning; Romeo, Saverio; Tsouri, Maria
ABSTRACT: This paper explores the divergence in patterns of regional development in twin towns, one in France, Grenoble, and one in the UK, Oxford. Since the early 2000s, a number of changes in national policies in each country have had a direct effect on the dynamics of local technology-led economic development. Here the particular interest is in those that relate to interrelationships (dyads) between anchor organizations (public sector research laboratories) and major local firms. The paper's focus is on how changes in policy effect strong local relationships and how multiple anchor organizations drive cluster development.